Evaluation of the Immune Response Afforded by Combined Immunization with Orf Virus DNA and Subunit Vaccine in Mice - Yan Wang; Kui Zhao; Deguang Song; Le Du; Xinyue Wang; Feng Gao; Huijun Lu; Jiyu Guan (Vaccines, 2022)
Contagious ecthyma (Orf) is a highly contagious disease caused by Orf virus (ORFV) infection. Orf is prevalent all over the world and, not only affects the healthy development of sheep husbandry, but also threatens human health. However, there are no safe and effective vaccines or drugs for the prevention and treatment of Orf at present. In this study, we constructed a DNA plasmid expressing ORFV B2L and F1L genes as a DNA vaccine candidate, with purified B2L full-length protein and F1L truncated protein as subunit vaccine candidates. BALB/c mice were immunized with the DNA vaccine, subunit vaccine, as well as DNA prime-protein boost strategies. The results showed that compared with the DNA vaccine and subunit vaccine alone, the DNA prime-protein boost immunization group had a higher level of specific antibodies, stronger lymphocyte proliferation, and higher expression of cytokines such as IL-2, IL-4, IL-6, IFN-γ, and TNF-α, which are considered to cause a Th1/Th2 mixed cytokine response. Our results demonstrated that the DNA prime-protein boost immunization strategy induced stronger humoral and cellular immune responses, which have potential advantages in preventing ORFV infection.